A method for regulating the crystal habit of empagliflozin based on deep eutectic solvent
By regulating the growth of empagliflozin crystals through low eutectic solvents to form regular cubic or flake crystals, the problems of poor fluidity and compressibility of empagliflozin crystals were solved, and environmentally friendly and efficient crystal regulation and drug preparation production were achieved.
Patent Information
- Application Number
- CN202510954399.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-09-05
- Estimated Expiration
- 2045-07-11
AI Technical Summary
Existing technologies make it difficult to effectively regulate the crystal habit of empagliflozin, resulting in poor crystal fluidity and insufficient compressibility, which affects the processing and solubility of drug preparations. Traditional solvent regulation methods rely on experience and are not environmentally friendly.
A low eutectic solvent formed by a mixture of tetrabutylammonium chloride and maleic acid is used to precisely regulate the growth of empagliflozin crystals through electrostatic interactions and hydrogen bond networks to form cubic or lamellar crystal habits. Combined with vacuum filtration and ethanol washing steps, the purity of the crystals is ensured.
The controllable morphology of empagliflozin crystals is achieved, the fluidity and compressibility are improved, the production costs are reduced, environmental protection requirements are met, the product is suitable for industrial production, and the processing efficiency and quality of drug preparations are improved.
Smart Images

Figure CN120463696B_ABST
Abstract
Description
Technical Field
[0001] The present invention application belongs to the field of medical technology and relates to a method for precisely regulating the crystal habit of empagliflozin based on a low eutectic solvent. Background Art
[0002] As a core drug for the treatment of type 2 diabetes, empagliflozin inhibits renal glucose reabsorption to achieve urinary glucose excretion, offering advantages such as weight loss, blood pressure reduction, and uric acid reduction, while minimizing the risk of hypoglycemia. It is widely used clinically. As the number of diabetes patients continues to grow globally, demand for its APIs is surging, and the requirements for quality and performance are becoming increasingly stringent.
[0003] Existing patent applications related to empagliflozin (such as CN101155794A and CN119080759A) primarily focus on polymorph protection (e.g., stabilizing Forms A and B) or chemical modification (e.g., acetylation). While these can improve the purity and stability of the polymorphs, the polymorph only determines the molecular arrangement and fails to address the practical challenges posed by the macroscopic crystal morphology in formulation processing. For example, Form A has a solubility of only 0.0299 mg / mL and poor crystal flowability (angle of repose > 40°), leading to issues such as uneven tablet weight and delayed disintegration during tablet compression. Crystal habit (crystal morphology) directly impacts key physical properties of the API, such as flowability, compressibility, and dissolution rate, but existing technologies lack effective means to regulate it. Current approaches to regulating the crystal habit of empagliflozin rely on traditional solvents such as ethanol and ethyl acetate, achieving limited control through polarity matching. The crystal habit has a low degree of regularity (60-80%) and relies on trial and error.
[0004] Currently, deep eutectic solvents (DESs) hold great potential in the field of pharmaceutical crystallization due to their designability, excellent solubility, and environmental friendliness (e.g., the use of CN118084788A to manipulate carbamazepine crystal forms). However, mature technologies for precisely manipulating the crystal habit of empagliflozin API have yet to be developed. Therefore, developing new methods based on novel DESs that are simple to operate and effectively manipulate the crystal habit of empagliflozin is of great significance for improving API quality, optimizing formulation performance, and meeting market demand. This approach is expected to bring innovative breakthroughs to the R&D and production of empagliflozin. Summary of the Invention
[0005] The present invention provides a method for precisely controlling the crystal habit of empagliflozin based on a deep eutectic solvent, aiming to partially or completely solve the technical problems in the prior art such as how to control the crystal habit of empagliflozin based on a deep eutectic solvent and prepare empagliflozin raw materials. The present invention achieves precise control of the growth of empagliflozin crystals under mild conditions by preparing a deep eutectic solvent, so that it forms a cubic or lamellar crystal habit, thereby ensuring the controllability, fluidity, compressibility and solubility of the crystal habit of empagliflozin. In order to achieve the purpose of the present invention, the technical solution of the present invention is as follows:
[0006] In the first aspect, a method for precisely controlling the crystal habit of empagliflozin based on a deep eutectic solvent comprises:
[0007] Step S100: Tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2-1:5, and stirred to react to form a homogeneous liquid solvent, thereby preparing a deep eutectic solvent;
[0008] Step S200: adding the empagliflozin raw material to a deep eutectic solvent to control the concentration to 5-15 mg / mL, stirring and dissolving, and cooling the solution to allow the empagliflozin to form a cubic crystal habit and / or a lamellar crystal habit;
[0009] Step S300: After the crystallization is completed, the crystals are separated from the deep eutectic solvent by filtration under reduced pressure, the crystals are washed, and dried to a constant weight.
[0010] The present invention provides a method for precisely controlling the crystal habit of empagliflozin based on a low eutectic solvent. When empagliflozin forms a cubic crystal habit, the electrostatic interaction between the maleic acid and tetrabutylammonium chloride ion pairs and the steric hindrance effect of the long-chain alkyl group of tetrabutylammonium chloride inhibit the growth of the (002) polar plane, causing the crystal growth rates in all directions to converge to form a cube; when empagliflozin forms a lamellar crystal habit, maleic acid combines with the aromatic ring and hydroxyl group of empagliflozin through double hydrogen bonds to inhibit the growth of the (101) non-polar plane, and tetrabutylammonium chloride weakens the growth driving force in the direction perpendicular to the (002) polar plane through electrostatic interaction, causing the crystal to extend two-dimensionally in a direction parallel to the (002) plane to form a thin sheet.
[0011] Optionally, in step S100, the reaction is stirred at 50-60°C for 2-4 hours; and / or, in step S200, the solution is stirred and dissolved at 40-50°C, and the solution is slowly cooled to 30-35°C at a cooling rate of 0.5-2°C / min; and / or, in step S300, the crystals are washed with ethanol and vacuum dried at 45-55°C and 1-3 kPa to constant weight.
[0012] Optionally, in step S200 , the deep eutectic solvent in step S300 is reused multiple times.
[0013] Optionally, in step S200, the deep eutectic solvent can be recycled for 8 times or less.
[0014] Optionally, tetrabutylammonium chloride acts as a hydrogen bond acceptor and maleic acid acts as a hydrogen bond donor, and the tetrabutylammonium chloride quaternary ammonium cation and the maleic acid carboxylate anion are tightly bound to each other through an ion pair effect to form a dynamic hydrogen bond network, and the hydrophobic chains enhance the layered stacking.
[0015] Optionally, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3.5 to 1:5, empagliflozin forms a cubic habit; or, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2 to 1:3, empagliflozin forms a lamellar habit; or, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3 to 1:3.5, empagliflozin forms a mixed lamellar and cubic habit.
[0016] In the second aspect, an empagliflozin drug with controllable crystal habit is prepared by any of the methods described in the first aspect for precisely controlling the crystal habit of empagliflozin based on a low eutectic solvent, wherein the empagliflozin drug has a cubic or lamellar crystal habit.
[0017] In the third aspect, the use of the empagliflozin raw material in the preparation of a pharmaceutical preparation for treating type 2 diabetes, wherein the empagliflozin drug is the empagliflozin drug with controllable crystal habit described in the second aspect above.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) In the present invention, firstly, the preparation of the low eutectic solvent only requires simple mixing, heating and stirring operations, and the crystallization control process of the empagliflozin API also only requires conventional steps such as dissolution, stirring, cooling crystallization, filtration and drying. The operation process is clear and easy to master, and there is no need for large-scale transformation of the existing pharmaceutical production line. It can be directly applied to industrial production. In addition, tetrabutylammonium chloride and maleic acid are relatively cheap, and the low eutectic solvent formed has good reusability, a small amount of addition, and does not introduce a complicated post-processing process, which effectively reduces production costs. At the same time, this method can reduce the production of unqualified products, improve production efficiency, and further save costs. The low eutectic solvent has low volatility and is more environmentally friendly than traditional organic solvents. It meets the requirements of sustainable development of the current pharmaceutical industry and helps companies establish a good social image.
[0020] (2) In the present application, the prepared cubic or flaky empagliflozin API has significantly improved flowability and compressibility. The angle of repose of the cubic crystals can be reduced to about 30°, and the flaky crystals have good formability during tablet compression. The tablet hardness and friability meet the pharmacopoeial standards, significantly improving the efficiency and quality of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the microscope structure of the three-dimensional crystal habit of empagliflozin applied for in the present invention.
[0022] Figure 2 Schematic diagram of the microscope structure of the lamellar crystal habit of empagliflozin applied for in the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments; multiple times include once or twice or more than twice; the numerical range can at least be understood to include the endpoint values, and can also be reasonably understood based on actual conditions; based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] A method for precisely regulating the crystal habit of empagliflozin based on deep eutectic solvents
[0025] In the first aspect, a method for precisely controlling the crystal habit of empagliflozin based on a deep eutectic solvent comprises:
[0026] Step S100: Tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2-1:5, and stirred to react to form a homogeneous liquid solvent, thereby preparing a deep eutectic solvent;
[0027] Specifically, step S100 includes: mixing tetrabutylammonium chloride and maleic acid in a molar ratio of 1:2-1:5, stirring and reacting at 50-60° C. for 2-4 hours to form a homogeneous liquid solvent, thereby preparing a deep eutectic solvent.
[0028] In some embodiments, a deep eutectic solvent (DES) is a low melting point mixture formed by two or more components through hydrogen bonding or other intermolecular forces (such as van der Waals forces), and its melting point is significantly lower than the individual melting points of each component.
[0029] In some embodiments, tetrabutylammonium chloride (TBACl) is a quaternary ammonium salt that acts as a hydrogen bond acceptor (HBA). Its structure provides strong electrostatic interactions, and its large molecular size allows for tunable crystal face adsorption selectivity. Maleic acid (Maleic Acid) acts as a hydrogen bond donor (HBD). Its dicarboxylic acid groups can form multiple hydrogen bonds, combining polarity with π-π conjugation, guiding crystal growth along specific crystal faces. The quaternary ammonium salt forms ion pairs with the maleic acid carboxylic acid groups through electrostatic interactions, forming a dynamic hydrogen bond network. The hydrophobic chains enhance lamellar stacking. A molar ratio of 1:2 to 1:5 ensures a sufficient number of maleic acid hydrogen bond donors, promoting the formation of a stable eutectic system. Under heating and stirring at 50-60°C for 2-4 hours, molecular thermal motion is enhanced, promoting hydrogen bond formation, and the mixture gradually transforms into a homogeneous liquid. Heating and stirring accelerate intermolecular interactions, reduce the system viscosity, and ensure thorough mixing of the components, resulting in the formation of a stable eutectic system.
[0030] In the present application, tetrabutylammonium chloride and maleic acid are relatively cheap raw materials. The preparation process of the low eutectic solvent does not use volatile organic solvents, which complies with the principles of green chemistry and reduces environmental pollution. The raw materials are easily available and inexpensive. The preparation process is simple and does not require complex equipment. It is suitable for industrial production. The mild temperature of 50-60°C and the reaction time of 2-4 hours have low energy consumption, safe operation, and easy control. The low eutectic solvent has high polarity, low viscosity and good solubility, which can effectively dissolve the empagliflozin raw material and promote the subsequent crystallization process. The flexible adjustment of the molar ratio of 1:2-1:5 and temperature conditions can optimize the physicochemical properties of the solvent, adapt to the crystallization requirements of different drugs, and provide an efficient and environmentally friendly solvent system for the subsequent empagliflozin crystallization.
[0031] Step S200: adding the empagliflozin raw material to a deep eutectic solvent to control the concentration to 5-15 mg / mL, stirring and dissolving, and cooling the solution to allow the empagliflozin to form a cubic crystal habit and / or a lamellar crystal habit;
[0032] Specifically, step S200 includes: adding the empagliflozin raw material to a low eutectic solvent, controlling the concentration to 5-15 mg / mL, stirring and dissolving at 40-50°C, and slowly cooling the solution to 30-35°C at a cooling rate of 0.5-2°C / min, so that the empagliflozin forms cubic and / or lamellar crystals.
[0033] In some embodiments, empagliflozin comprises a (002) polar face and a (101) non-polar face. The (002) polar face can expose polar groups (such as hydroxyl or chlorine atoms) in the molecule, resulting in an asymmetric surface charge distribution and forming a net dipole moment. The polar face generally affects solubility and bioavailability. The (101) non-polar face can have a more symmetrical atomic arrangement, a uniform distribution of polar groups, and a symmetrical charge distribution. The non-polar face is generally more stable and can be used as the primary exposed face during crystal growth and drug formulation.
[0034] In some embodiments, empagliflozin is a small molecule drug (SGLT2 inhibitor) that dissolves in deep eutectic solvents (e.g., tetrabutylammonium chloride-maleic acid DES) through intermolecular interactions (e.g., electrostatic, hydrogen bonding, and hydrophobic). The strong solubility and low volatility of DES make it a suitable crystallization medium. The viscosity and dynamic hydrogen bonding network of DES influence the direction of crystal growth. Empagliflozin molecules form (regular) cubic or plate-shaped crystals (depending on the molar ratio) in DES through specific intermolecular forces (e.g., electrostatic, hydrogen bonding, and hydrophobic) that are closely related to the solvent properties and the cooling rate. In some embodiments, heating at 40-50°C enhances molecular thermal motion, accelerates empagliflozin dissolution, and avoids decomposition of DES or empagliflozin. The concentration is controlled at 5-15 mg / mL to form a homogeneous solution, ensuring that the solution is not oversaturated, which is conducive to subsequent crystal growth. Slow cooling to 30-35°C reduces solubility, creates moderate supersaturation, and promotes crystal formation.
[0035] Furthermore, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3.5 to 1:5 (i.e., greater than or equal to 1:5 and less than or equal to 1:3.5), empagliflozin forms a cubic crystal habit. The electrostatic interaction between the maleic acid and tetrabutylammonium chloride ion pairs and the steric hindrance effect of the long-chain alkyl group of tetrabutylammonium chloride inhibit the growth of the (002) polar plane, causing the crystal growth rate in all directions to converge, forming a cube.
[0036] Specifically, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3.5 to 1:5 (i.e., greater than or equal to 1:5 and less than or equal to 1:3.5), empagliflozin forms a cubic crystal habit. The carboxylate anion generated by the ionization of maleic acid forms an ion pair with the tetrabutylammonium chloride quaternary ammonium cation, which is specifically adsorbed on the (002) polar face of empagliflozin through electrostatic interaction. At the same time, the hydrophobic layer formed by the long-chain alkyl group of the tetrabutylammonium chloride quaternary ammonium cation inhibits the growth of the (002) polar face through the steric hindrance effect. The high degree of ionization of maleic acid weakens the double hydrogen bond effect and cannot inhibit the growth of the (101) non-polar face. The growth of the (101) non-polar face eventually makes the crystal growth rate converge in all directions, forming a cube.
[0037] Furthermore, when empagliflozin forms a lamellar crystal habit, maleic acid binds to the aromatic ring and hydroxyl group of empagliflozin through double hydrogen bonds to inhibit the growth of the (101) non-polar plane, and tetrabutylammonium chloride weakens the growth driving force in the direction perpendicular to the (002) polar plane through electrostatic interaction, causing the crystal to extend two-dimensionally in a direction parallel to the (002) plane to form a thin sheet.
[0038] Specifically, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2~1:3 (i.e., greater than or equal to 1:3 and less than or equal to 1:2), the maleic acid molecules bind to the aromatic ring and hydroxyl group of empagliflozin through double hydrogen bonds, preferentially adsorb on the (101) non-polar surface, and inhibit its growth; the positive charge of the quaternary ammonium cation of tetrabutylammonium chloride shields the polar interactions between empagliflozin molecules through electrostatic action, weakening the growth driving force in the direction perpendicular to the (002) polar surface, causing the crystal to extend two-dimensionally in the direction parallel to the (002) surface to form thin sheets.
[0039] Furthermore, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3 to 1:3.5 (i.e., greater than 1:3.5 and less than 1:3), empagliflozin forms a mixed crystal habit of flakes and cubes. The maleic acid molecules inhibit the growth of the (101) non-polar face through double hydrogen bond adsorption, and the ion pairs formed by the carboxylate anions produced by ionization and the quaternary ammonium cations of tetrabutylammonium chloride inhibit the growth of the (002) polar face through electrostatic adsorption. The two inhibitory effects antagonize each other, reducing the difference in growth rate in the two directions of the crystal. In addition, the influence of the system microenvironment causes different regions to exhibit flake or cube growth characteristics, thereby forming a mixed morphology. Ultimately, empagliflozin forms a mixed crystal habit of cubes and flakes.
[0040] In some embodiments, a cooling rate of 0.5-2°C / min provides sufficient time for the empagliflozin molecules to arrange in an orderly manner to form (regular) crystals (cubic and / or lamellar), and the dynamic hydrogen bond network and polar environment of the deep eutectic solvent guide the crystal morphology.
[0041] In the present application, firstly, the dissolution temperature of 40-50°C and the cooling rate of 0.5-2°C / min can be adjusted as needed to optimize the crystal morphology (such as cubic or flake-shaped). Slow cooling (30-35°C) and concentration control (5-15 mg / mL) promote the growth of crystals (cubic or flake-shaped), improve the crystal uniformity and morphology, enhance the physical properties of the drug, ensure that the crystal growth process is controlled, and avoid irregular crystals caused by rapid precipitation. In addition, the high polarity and solubility of the low eutectic solvent ensure that empagliflozin dissolves rapidly under mild conditions (40-50°C), shortening the preparation time. The formation of regular crystals also reduces defects between particles and improves the stability and consistency of subsequent processing (such as tableting).
[0042] Step S300: After the crystallization is completed, the crystals are separated from the deep eutectic solvent by filtration under reduced pressure, and the crystals are washed and dried to a constant weight.
[0043] Specifically, step S300 includes: after the crystallization is completed, separating the crystals from the low eutectic solvent by filtration under reduced pressure, washing the crystals with ethanol, and vacuum drying at 45-55° C. and 1-3 kPa to constant weight.
[0044] In some embodiments, a conventional Büchner funnel, vacuum pump, filter paper or filter cloth, receiving bottle, etc. can be used to form a reduced pressure filtration system. The crystallization mixture is poured into the Büchner funnel. The filter paper is pre-laid and moistened to ensure sealing. The vacuum pump is started to reduce the system pressure. The liquid is pumped into the receiving bottle, and the crystals remain on the filter paper. The filtration is continued until the liquid is basically drained.
[0045] In the present application, reduced pressure filtration (also known as vacuum filtration) reduces the pressure inside the filtration device and uses the pressure difference between atmospheric pressure and the pressure inside the device to drive the liquid through the filter membrane or filter cloth to quickly separate solid crystals and liquid (deep eutectic solvent). The deep eutectic solvent is usually a low-melting-point, easy-flowing liquid mixture. Reduced pressure filtration can efficiently separate crystals and separate crystals from the solvent to obtain a pure solid product, while reducing liquid residue and improving subsequent drying efficiency.
[0046] In some embodiments, after filtration under reduced pressure, an appropriate amount of analytical grade ethanol is slowly added to the filter cake (crystals) to cover the crystal surface, and filtration is continued to allow ethanol to pass through the filter cake, removing residual low eutectic solvent and impurities. Washing can be repeated 1-2 times to ensure a clean crystal surface.
[0047] In this application, ethanol is used as a detergent because of its good solubility, dissolving any residual deep eutectic solvent or other impurities on the crystal surface. Ethanol is also highly volatile, making it easy to remove during subsequent drying without leaving any residue. The washing process cleans the crystal surface through physical dissolution and displacement, improving crystal purity.
[0048] In some embodiments, a vacuum drying oven or vacuum oven can be used, equipped with temperature control and a vacuum pump, to transfer the washed crystals to a drying dish or tray, and place the washed crystals in a vacuum drying oven or vacuum oven. The temperature is set to 45-55°C and the vacuum degree is set to 1-3 kPa. The crystals are weighed regularly until the weight no longer changes (constant weight), which usually takes several hours to a day.
[0049] In this application, the boiling point of ethanol and other volatile substances is lowered by reducing the pressure under vacuum conditions of 45-55°C and 1-3 kPa, thereby accelerating evaporation and drying. Constant weight refers to the crystalline weight no longer changing, indicating that the solvent and water have been completely removed, ensuring that the empagliflozin product is dry, stable, and suitable for subsequent storage or use.
[0050] In this invention, the preparation of the deep eutectic solvent requires only simple mixing, heating, and stirring operations. The crystallization control process for the empagliflozin API also requires only conventional steps such as dissolution, stirring, cooling, crystallization, filtration, and drying. The operational flow is clear and easy to master, eliminating the need for large-scale modifications to existing pharmaceutical production lines and enabling direct application in industrial production. Furthermore, tetrabutylammonium chloride and maleic acid are relatively inexpensive, and the deep eutectic solvent is reusable, requiring minimal addition and eliminating the need for complex post-processing, effectively reducing production costs. Furthermore, this method can reduce the production of substandard products, improve production efficiency, and further reduce costs. The low volatility of the deep eutectic solvent makes it more environmentally friendly than traditional organic solvents, meeting the current requirements for sustainable development in the pharmaceutical industry and helping companies establish a positive social image.
[0051] Optionally, in step S200 , the deep eutectic solvent separated in step S300 is reused multiple times.
[0052] In some embodiments, the deep eutectic solvent can be recycled 8 times or less while still maintaining the ability to control the crystal habit.
[0053] In the present application, in step S200, the recovered DES undergoes simple treatment (e.g., filtration to remove trace residual solids or addition of a small amount of tetrabutylammonium chloride / maleic acid to adjust the molar ratio) and can be reused in the dissolution and crystallization process of step S200. The ionic mobility (provided by tetrabutylammonium chloride) and hydrogen bond network (provided by maleic acid) of DES are not easily destroyed during multiple cycles, thereby maintaining its molecular regulation ability as a solvent.
[0054] In the present application, tetrabutylammonium chloride and maleic acid are cheap raw materials, and the preparation cost of DES is much lower than that of traditional organic solvents (such as methanol and acetonitrile). The stability and reusability of DES reduce solvent consumption and can further reduce production costs. DES can be recovered by vacuum filtration with a low loss rate, and repeated use significantly reduces the need for solvent replenishment and replacement frequency. The recovered DES can be reused directly or after simple treatment (such as filtration or raw material replenishment), without the need for complex purification steps, simplifying the process flow, reducing the need for solvent waste treatment, reducing environmental pollution risks and processing costs, and improving production efficiency. DES maintains its solubility (5-15 mg / mL) and molecular regulation ability (inducing cubic or flaky crystals) in multiple cycles, ensuring the consistency of the quality of empagliflozin crystals (such as fluidity, compressibility, dissolution rate, etc.), supporting a green and efficient empagliflozin crystallization process, and is suitable for continuous industrial production.
[0055] In the second aspect, an empagliflozin drug with controllable crystal habit is prepared by any of the methods described in the first aspect for precisely controlling the crystal habit of empagliflozin based on a low eutectic solvent, wherein the empagliflozin drug has a cubic or lamellar crystal habit.
[0056] In this application, the prepared cubic or flaky empagliflozin API exhibits significantly improved flowability and compressibility. The angle of repose of the cubic crystals can be reduced to approximately 30°, and the flaky crystals exhibit excellent formability during tablet compression. The tablet hardness and friability meet pharmacopoeial standards, significantly improving the efficiency and quality of the formulation.
[0057] In the third aspect, the use of the empagliflozin raw material in the preparation of a pharmaceutical preparation for treating type 2 diabetes, wherein the empagliflozin drug is the empagliflozin drug with controllable crystal habit described in the second aspect above.
[0058] Unless otherwise specified, the raw materials and reagents used in the following experiments are commercially available products or reagents prepared according to conventional methods. Unless otherwise specified, the methods used in the experiments are conventional experimental methods. Unless otherwise specified, the instruments used in the experiments are commercially available.
[0059] Example 1
[0060] (1) Tetrabutylammonium chloride and maleic acid were mixed in a molar ratio of 1:4, added to a round-bottom flask, and stirred in an oil bath at 50°C at a speed of 200 r / min for 3 hours to obtain a deep eutectic solvent;
[0061] (2) Crystallization process: 100 mg of empagliflozin raw material was added to 10 mL of the above-mentioned deep eutectic solvent and stirred at 45°C at a speed of 200 r / min for 45 minutes until completely dissolved; then the solution was cooled to 30°C at a cooling rate of 0.8°C / min. During this process, empagliflozin crystals gradually precipitated, and the crystallization time was 8 hours;
[0062] (3) The crystals were separated from the deep eutectic solvent by vacuum filtration and washed four times with 50 mL of ethanol, each time for 8 minutes. The crystals were placed in a vacuum drying oven and dried at 50°C and 2 kPa for 10 hours to obtain the empagliflozin API. Microscopic observation showed that the crystals had a cubic structure.
[0063] Example 2
[0064] (1) Tetrabutylammonium chloride and maleic acid were mixed in a molar ratio of 1:3 and stirred in an oil bath at 55°C for 3.5 hours to prepare a deep eutectic solvent;
[0065] (2) 120 mg of empagliflozin raw material was added to 12 mL of deep eutectic solvent and stirred at 48°C at a speed of 220 r / min for 50 minutes until completely dissolved; then the solution was cooled to 30°C at a cooling rate of 1°C / min to promote the crystallization of empagliflozin crystals, and the crystallization time was 7 hours;
[0066] (3) The crystals were separated from the deep eutectic solvent by vacuum filtration and washed three times with 60 mL of ethanol for 10 minutes each time. The crystals were dried at 48°C and 1.5 kPa for 11 hours to obtain empagliflozin API in the form of flakes. Microscopic observation showed that the crystals had a flake structure with a thickness of approximately 1.1 μm and a length of approximately 8 μm.
[0067] Example 3
[0068] (1) Tetrabutylammonium chloride and maleic acid were mixed in a molar ratio of 1:3.2, added to a round-bottom flask, and stirred in an oil bath at 50°C at a speed of 200 r / min for 3 hours to obtain a deep eutectic solvent;
[0069] (2) Crystallization process: 100 mg of empagliflozin raw material was added to 10 mL of the above-mentioned deep eutectic solvent and stirred at 45°C at a speed of 200 r / min for 45 minutes until completely dissolved; then the solution was cooled to 35°C at a cooling rate of 0.8°C / min. During this process, empagliflozin crystals gradually precipitated, and the crystallization time was 8 hours;
[0070] (3) The crystals were separated from the deep eutectic solvent by vacuum filtration and washed four times with 50 mL of ethanol, each time for 8 minutes. The crystals were placed in a vacuum drying oven and dried at 50°C and 2 kPa for 10 hours to obtain the empagliflozin API. Microscopic observation showed that the crystals consisted of a mixed structure of cubic and flake structures.
[0071] Comparative Example 1
[0072] 100 mg of empagliflozin raw material was dissolved in 10 mL of ethanol-water (volume ratio 1:1) mixed solvent, stirred at 45°C until completely dissolved, and then slowly cooled to 32°C at a cooling rate of 1°C / min for crystallization.
[0073] Flowability, compressibility, and dissolution rate determination
[0074] Angle of repose determination: A funnel was mounted on a stand with the lower opening of the funnel 20 cm vertically above a horizontal circular base. An appropriate amount of the empagliflozin API prepared in Example 1, Example 2, and Comparative Example 1 was slowly poured into the funnel, allowing the drug to freely fall and accumulate on the base until a stable conical accumulation was formed. The angle between the generatrix of the accumulation and the horizontal plane was measured using an angle measuring instrument. Three replicate measurements were performed for each sample, and the average value was taken as the angle of repose.
[0075] Compressibility Test: 5 g of each of the empagliflozin APIs prepared in Example 1, Example 2, and Comparative Example 1 were added to the mold of a powder tablet press and compressed under a compressive force of 10 kN for 30 seconds into round tablets with a diameter of 10 mm. The radial hardness of the tablets was measured using a durometer. Five tablets were prepared for each sample, and the average hardness was taken as the tablet hardness.
[0076] Dissolution rate determination: Using the paddle method, according to the "Chinese Pharmacopoeia 2020 Edition, Part IV, 0931, Dissolution and Release Determination Method," the dissolution medium (900 mL of 0.1 mol / L hydrochloric acid solution) was heated to 37°C ± 0.5°C and the paddle speed was set at 50 r / min. 100 mg of each of the empagliflozin API prepared in Example 1, Example 2, and Comparative Example 1 was placed into a dissolution vessel. At 5, 10, 15, 20, and 30 minutes, 5 mL of solution was drawn from the dissolution vessel using a syringe (simultaneously supplemented with 5 mL of the dissolution medium at the same temperature). The drawn solution was filtered through a 0.45 μm filter membrane, and the empagliflozin concentration in the solution was determined by HPLC. Dissolution curves were plotted, and the cumulative amount of drug dissolved at different time points was calculated.
[0077] The results of the flowability, compressibility, and dissolution rate measurements of the empagliflozin APIs prepared in Examples 1 and 2 and the empagliflozin prepared in Comparative Example 1 are as follows:
[0078]
[0079] It can be seen that the empagliflozin crystals obtained in Comparative Example 1 have irregular shapes, poor fluidity and compressibility, and are difficult to meet the requirements for preparation production.
[0080] (1) Habit analysis
[0081] Crystal habit refers to the appearance and microstructure of crystals, which directly affect the physical properties and processing characteristics of drugs. The cubic crystals of Example 1 are highly regular and suitable for scenarios requiring uniform particles. The flaky crystals of Example 2 have a large contact area. The flaky crystals (lamellar thickness is approximately 1.1 μm, and length is approximately 8 μm) have a large aspect ratio and planar area, resulting in a large contact area between particles, which easily forms layered stacking and may affect flowability. The crystal morphology of Comparative Example 1 is irregular, and the contact between particles is complex, which may lead to uneven stacking, verifying the superiority of the low eutectic solvent preparation method. The reasons for the crystal habit results are as follows:
[0082] 1) Solvent system: The low eutectic solvent composed of tetrabutylammonium chloride and maleic acid guides the arrangement of empagliflozin molecules through a triple mechanism of electrostatic interaction (the quaternary ammonium cation of tetrabutylammonium chloride and the hydroxyl group of empagliflozin Coulomb force adsorption inhibits the (002) polar surface), double hydrogen bond network (the carboxylic acid group of maleic acid forms double hydrogen bonds with the amino group / hydroxyl group of the aromatic ring of empagliflozin to inhibit the (101) non-polar surface), π-π stacking and hydrophobic effect (the double bond of maleic acid and the π-π stacking of the aromatic ring, and the hydrophobic interaction of the long chain alkyl of tetrabutylammonium chloride to form a layered arrangement), and regulates the crystal surface growth by the molar ratio (cubic formation at 1:4 and lamellar formation at 1:3). In contrast, the ethanol-water system only dissolves the drug through nonspecific polarity matching, lacks directional effect and has large fluctuations in supersaturation, resulting in disordered growth of crystals and irregular morphology.
[0083] 2) Cooling Control: A slow cooling rate of 0.5-2°C / min allows the molecules to gradually settle in the solution, forming regular cubic crystals. The lower supersaturation (30-35°C) reduces the rapid formation of crystal nuclei, allowing the empagliflozin molecules ample time to deposit in an orderly manner along thermodynamically stable crystal planes, favoring the development of larger, regular crystals. Alternatively, it promotes rapid expansion of the molecules along a specific crystal plane, resulting in a larger aspect ratio (length 8μm / thickness 1.1μm).
[0084] 3) Stirring and crystal nucleus control: Stirring at 40-50°C may introduce slight shear force, affecting the growth direction of the crystal nucleus and allowing it to develop into thin flake crystals.
[0085] (2) Liquidity analysis
[0086] Flowability is measured by the angle of repose, which reflects the powder's ability to flow under gravity. The smaller the angle of repose, the better the flowability. The empagliflozin APIs of Examples 1 and 2 exhibited better flowability than those of Comparative Example 1. The cubic and flaky crystals facilitated powder flow and were therefore suitable for subsequent processing. Specifically:
[0087] Example 1 (angle of repose 31°) has a smaller angle of repose and better fluidity. Combined with crystal habit analysis, the cubic crystals have a flat surface, low interparticle friction, and good slip when stacked, resulting in excellent fluidity. Example 2 (angle of repose 32°) has a slightly larger angle of repose than Example 1, but is still within the range of good fluidity (generally, an angle of repose <35° indicates good fluidity). The lamellar crystals may have a slightly stronger adsorption force between particles due to their larger contact area, but the lamellar structure facilitates slip, resulting in good fluidity. Comparative Example 1 (angle of repose 47°) has a significantly larger angle of repose, indicating poor fluidity (generally, an angle of repose >40° indicates poor fluidity). It is speculated that the irregular crystal morphology leads to high interparticle friction, easily forming an unstable structure when stacked, and limiting fluidity.
[0088] The reasons for the liquidity results are as follows:
[0089] 1) Crystal morphology: Crystal habit is a key factor influencing fluidity. The cubic crystals of Example 1 exhibit strong regularity, a smooth surface, low friction, and optimal fluidity. While the flake-shaped crystals of Example 2 exhibit slightly increased resistance due to their large contact area, their layered structure still supports good slip. The irregular crystal morphology of Comparative Example 1 results in uneven particle shape and size distribution, a rough surface, and high inter-particle friction. When stacked, the particles are unable to slide freely, forming an unstable stacking structure, resulting in a large angle of repose and the worst fluidity.
[0090] 2) Regulation of preparation conditions: The deep eutectic solvent (tetrabutylammonium chloride and maleic acid) forms a multiple intermolecular interaction network through electrostatic adsorption between the quaternary ammonium cation and the hydroxyl group of empagliflozin, double hydrogen bonding between the maleic acid carboxylic acid group and the aromatic ring, and π-π stacking effect between the double bond and the aromatic ring. This directionally inhibits the growth of specific crystal planes and guides the orderly arrangement of molecules, thereby regulating the growth of crystals (cubic or lamellar). Examples 1 and 2 achieve better crystal habits and fluidity. However, the ethanol-water solvent of Comparative Example 1 lacks similar regulation, resulting in disordered crystal morphology and limited fluidity.
[0091] 3) Interaction between particles: The surfaces of cubic and lamellar crystals are relatively smooth, the friction between particles is small, and the slippage is good. Cubic crystals have fewer contact points. Although lamellar crystals have a large contact area, their layered structure supports slippage, and the particle size distribution is uniform, which reduces the stacking instability caused by uneven particles, forms a smaller repose angle, and improves fluidity. The surface of irregular crystals is rough, the contact between particles is complex, the friction and adsorption force are large, and it is difficult for particles to slide freely when stacked, forming a high-angle stack with a large repose angle and poor fluidity, which worsens the fluidity.
[0092] (3) Compressibility analysis
[0093] Compressibility is measured by tablet hardness (radial hardness), which reflects the bonding ability and strength of the powder when compressed into tablets. The higher the hardness, the better the compressibility. The compressibility of the empagliflozin API in Examples 1 and 2 was superior to that of Comparative Example 1. The cubic and flaky crystals bonded more tightly during compression, making them suitable for preparing high-strength tablets. Specifically:
[0094] Example 1 (tablet hardness 83N) had the highest tablet hardness, indicating optimal compressibility. The cubic crystals exhibited strong regularity, resulting in uniform force between particles and tight bonding during compression, resulting in a dense tablet structure and high hardness. Example 2 (tablet hardness 81N) had a slightly lower hardness than Example 1, but still relatively high, indicating good compressibility. The flaky crystals had a large contact area, allowing for strong bonding between particles during compression. However, this may have resulted in slightly uneven local stress distribution, possibly due to the thin flaky layer thickness (1.1 μm). Comparative Example 1 (tablet hardness 53N) had significantly lower hardness and poorer compressibility. The irregular crystals exhibited uneven force between particles, resulting in insufficient bonding during compression, resulting in a loose tablet structure and low hardness.
[0095] The reasons for the compressibility results are as follows:
[0096] 1) Crystal morphology: Crystal morphology directly affects the force distribution and bonding ability of particles during compression. Regular cubic crystals experience uniform force during compression, with consistent contact points between particles, resulting in a tightly bound structure. The compression process forms strong bonds between particles, resulting in a dense tablet structure, the highest hardness (83N), and optimal compressibility. The larger contact area of flaky crystals promotes layered stacking between particles, forming a strong bond during compression. However, the thin flaky layer thickness (1.1μm) may lead to uneven local stress distribution. Especially under high pressure, the flakes may experience slight deformation or fracture, slightly affecting bonding strength, but maintaining good compressibility. Irregular crystals experience uneven force during compression, with inconsistent contact points between particles and insufficient bonding. This makes it difficult to form a dense structure during compression, resulting in loose tablets with low hardness and poor compressibility.
[0097] 2) Interparticle interaction: Particle shape and contact characteristics affect the bonding ability during compression. Cubic crystals have a smooth surface, low friction between particles, and form uniform bonding points during compression, enhancing the mechanical strength of the tablet. The larger contact area of flaky crystals increases the bonding force between particles, but the thin flake structure may cause local uneven stress and slightly reduce the hardness. Irregular crystals have a rough surface, complex contact between particles, and high friction, making it difficult to form effective bonds during compression, resulting in a loose tablet structure.
[0098] (4) Dissolution rate analysis
[0099] The dissolution rate is measured by the cumulative amount of dissolution (dissolution rate), reflecting the release rate of the drug in the dissolution medium. The higher the dissolution rate, the faster the drug dissolution rate. The dissolution rate of the empagliflozin API in Examples 1 and 2 is superior to that in Comparative Example 1. Cubic and flaky crystals are more conducive to rapid drug dissolution and are suitable for drug formulations requiring rapid onset of action. Specifically:
[0100] Example 2 (dissolution rate 1.4 mg / min) had the fastest dissolution rate, indicating the highest drug release efficiency. The dissolution rate of Example 2 (dissolution rate 1.4 mg / min) was slightly higher than that of Example 1. This is due to the larger specific surface area of the flaky crystals, which theoretically allows for a larger solvent contact area. Comparative Example 1 (dissolution rate 0.8 mg / min) had the lowest dissolution rate and poorer release efficiency. Irregular crystals may have led to uneven packing between particles, making it difficult for the solvent to evenly contact the particle surface, limiting the dissolution rate.
[0101] The reasons for the dissolution rate results are as follows:
[0102] 1) Influence of crystal morphology and specific surface area
[0103] The crystal morphology determines the surface properties of the particles and the solvent contact efficiency, which directly affects the dissolution rate. Cubic crystals have high regularity, a smooth surface, and a relatively small specific surface area. Although the specific surface area of cubic crystals is small, their regularity and uniformity ensure that the dissolution medium can evenly contact the particle surface, avoiding local accumulation or obstruction, resulting in high solvent penetration efficiency and a faster drug release rate (1.3 mg / min). The larger specific surface area of flaky crystals theoretically increases the solvent contact area. During the dissolution process, the larger the contact area between the drug molecules and the solvent, the more efficient the penetration and dissociation of the solvent molecules on the crystal surface. Therefore, the dissolution rate is faster, and the dissolution rate (1.4 mg / min) is slightly higher than that of Example 1. Irregular crystal particles are unevenly stacked, and some particle surfaces may be blocked by other particles, making it difficult for the solvent to evenly contact, reducing the dissolution efficiency. The dissolution rate of Comparative Example 1 is the lowest (0.8 mg / min) and the release efficiency is poor.
[0104] 2) Interparticle stacking characteristics: The particle stacking pattern affects the penetration and contact efficiency of the solvent. Cubic crystals have high regularity and the interparticle stacking is relatively loose, allowing the dissolution medium to penetrate the particle surface and promote rapid dissolution. Flake crystals have a large solvent contact area, and the solvent molecules are more efficient in penetrating and dissociating the crystal surface. The disordered stacking of irregular crystals forms an uneven structure, making it difficult for the solvent to penetrate into the interior of the particles, and the dissolution rate is significantly limited.
[0105] Effect of cycle number on the regulation of deep eutectic solvent
[0106] The deep eutectic solvent separated in Example 1 was recycled for the first time, the third time, the fifth time, the eighth time and the tenth time. The method for preparing the empagliflozin API in Example 1 was still used in the first time, the third time, the fifth time, the eighth time and the tenth time. The crystal habit, flowability, compressibility and dissolution rate of the deep eutectic solvent for preparing the empagliflozin API in the first cycle (referred to as Example 1), the deep eutectic solvent for preparing the empagliflozin API in the third cycle (referred to as Example 2), the deep eutectic solvent for preparing the empagliflozin API in the fifth cycle (referred to as Example 3), the deep eutectic solvent for preparing the empagliflozin API in the eighth cycle (referred to as Example 4) and the deep eutectic solvent for preparing the empagliflozin API in the tenth cycle (referred to as Example 5) were measured. The specific results are as follows:
[0107]
[0108] It can be seen that after the low eutectic solvent was recycled for 8 times, the crystal form of empagliflozin remained cubic and did not change significantly, indicating that the process stability was high. The angle of repose increased from 32° to 38°, the compressibility decreased from 81N to 65N, and the dissolution rate decreased from 1.2mg / min to 0.9mg / min, indicating that some physical properties of empagliflozin decreased slightly with the increase in the number of cycles. After 8 DES cycles, the overall quality of empagliflozin still basically met the preparation requirements.
[0109] (1) Habit analysis
[0110] In all cycles (from the 1st to the 10th), the crystal morphology of empagliflozin was a regular cubic crystal habit, indicating that the cyclic use of DES did not significantly change the crystal morphology of empagliflozin and maintained stable crystal growth conditions.
[0111] (2) Liquidity analysis
[0112] Fluidity, expressed as the angle of repose, was 32° in the first cycle and increased to 38° in the eighth cycle. This increase in the angle of repose indicates a slight decrease in fluidity, but it is still within an acceptable range (generally, an angle of repose < 40° is considered to meet most production requirements). The angle of repose was 42° in the tenth cycle, indicating that fluidity was affected. Recycling of deep eutectic solvents does affect fluidity.
[0113] (3) Compressibility analysis
[0114] Compressibility is expressed as tablet hardness (N), which was 81 N after the first cycle and dropped to 65 N after the eighth cycle. The gradual decrease in hardness indicates that compressibility weakens with increasing cycles. 65 N still has a certain tableting capacity, and the compressibility decreases significantly after the tenth cycle, reaching 58 N.
[0115] (4) Dissolution rate analysis
[0116] The dissolution rate is expressed as mg / min. The first cycle was 1.2 mg / min, and it dropped to 0.9 mg / min after the eighth cycle. The dissolution rate gradually decreased, indicating that the dissolution efficiency weakened with the increase in the number of cycles. There was still some dissolution performance at 0.9 mg / min, and the dissolution rate dropped significantly to 0.7 mg / min after the tenth cycle. The cyclic use of the deep eutectic solvent has an impact on the dissolution rate.
[0117] Therefore, in the present application, the prepared cubic or flaky empagliflozin raw material has significantly improved fluidity and compressibility, the angle of repose of the cubic crystals can be reduced to about 30°, the flaky crystals have good formability during the tablet pressing process, and the tablet hardness and friability meet the pharmacopoeia standards, which significantly improves the efficiency and quality of the preparation processing.
[0118] Those skilled in the art can understand that the various operations, methods, steps in the process, measures, and schemes discussed in the present invention application can be interchanged, changed, combined, or deleted; further, the various operations, methods, and other steps, measures, and schemes in the process discussed in the present invention application can also be interchanged, changed, rearranged, decomposed, combined, or deleted; further, the various operations, methods, and steps in the process disclosed in the present invention application in the prior art can also be interchanged, changed, rearranged, decomposed, combined, or deleted. The various technical features of the above embodiments can be arbitrarily combined. To make the description concise, not all possible combinations of the various technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification;
[0119] The embodiments described above only express several implementation methods of the embodiments of the present disclosure, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the patent scope of the embodiments of the present disclosure; it should be pointed out that for ordinary technicians in this field, without departing from the concept of the embodiments of the present disclosure, several variations and improvements can be made, which all fall within the protection scope of the embodiments of the present disclosure; therefore, the protection scope of the embodiments of the present disclosure should be based on the attached claims. As mentioned above, although the present invention application has been expressed and described with reference to specific preferred embodiments, it shall not be interpreted as limiting the present invention application itself. Various changes can be made to it in form and detail without departing from the spirit and scope of the present invention application defined in the attached claims.
[0120] The above description of the present invention and its embodiments is non-limiting. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if a person skilled in the art is inspired by this and, without departing from the inventive purpose of the present invention, designs structures and embodiments similar to the technical solution without inventiveness, they shall fall within the scope of protection of the present invention.
Claims
1. A method for regulating the crystal habit of empagliflozin based on a deep eutectic solvent, characterized in that: include: Step S100: Tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2-1:5, and stirred to react to form a homogeneous liquid solvent, thereby preparing a deep eutectic solvent; Step S200: adding the empagliflozin raw material to a deep eutectic solvent to control the concentration to 5-15 mg / mL, stirring and dissolving, and cooling the solution to allow the empagliflozin to form a cubic crystal habit and / or a lamellar crystal habit; Step S300: After the crystallization is completed, the crystals are separated from the deep eutectic solvent by filtration under reduced pressure, the crystals are washed, and dried to a constant weight; In step S100, stirring and reacting at 50-60° C. for 2-4 hours; In step S200 , the solution is stirred and dissolved at 40-50° C., and the temperature of the solution is slowly cooled to 30-35° C. at a cooling rate of 0.5-2° C. / min.
2. The method for regulating the crystal habit of empagliflozin based on a deep eutectic solvent according to claim 1, characterized in that: In step S300, the crystals are washed with ethanol and vacuum dried at 45-55°C and 1-3 kPa to a constant weight.
3. The method for regulating the crystal habit of empagliflozin based on a deep eutectic solvent according to claim 1, characterized in that: In step S200 , the deep eutectic solvent in step S300 is reused multiple times.
4. The method for regulating the crystal habit of empagliflozin based on a deep eutectic solvent according to claim 1, characterized in that: In step S200 , the deep eutectic solvent is recycled for less than or equal to 8 times.
5. The method for regulating the crystal habit of empagliflozin based on a deep eutectic solvent according to claim 1, characterized in that: When tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3.5 to 1:5, empagliflozin forms a cubic crystal habit; or, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:2 to 1:3, empagliflozin forms a lamellar crystal habit; or, when tetrabutylammonium chloride and maleic acid are mixed in a molar ratio of 1:3 to 1:3.5, empagliflozin forms a mixed lamellar and cubic crystal habit.
Citation Information
Patent Citations
Crystalline form of 1-chloro-4-(ss-d-glucopyranos-1-yl)-2-[4-((s)-tetrahydrofuran-3-yloxy)-benzyl]-benzene, a method for its preparation and the use thereof for preparing medicaments
CN101155794A
Method for preparing metastable crystal form carbamazepine
CN118084788A
Crystal form of acetylated empagliflozin and preparation method thereof
CN119080759A
A solid dispersion of amorphous empagliflozin and a preparing method thereof
CN106880595A
Empagliflozin-nicotinamide eutectic crystal and preparation method thereof
CN112062757A